PERAN GERAKAN BURUH DALAM MEMPERJUANGKAN KESEJAHTERAAN UPAH DI INDONESIA : (KAJIAN LITERATUR GERAKAN SERIKAT BURUH INDEPENDEN) - Pita, Anupita larasayu; Widiansyah, Subhan (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
This paper analyzes the social movements carried out by workers in demanding wage welfare. Through the analysis of the movement carried out by the Association of independent labor unions together with other workers in demanding the right to fulfillment and an increase in work wages. The government on the rules that stipulate the minimum wage often sided with the employers which was usually followed by a strike by the workers or workers. The root of this problem, of course, is usually triggered by the regulation of setting minimum wages, which workers consider inappropriate and inappropriate in providing minimum wages and demanding welfare for workers. The minimum wage has the aim of providing protection for workers from a small minimum wage, so that the minimum wage promotes the creation of justice for workers and also does not harm employers to fulfill the daily needs of the workers. Employers and workers both have the continuity of life which will also have an impact on the progress of the company, the government has a function in regulating decent wages for workers. The purpose of this analysis is to analyze the influence of the GSBI movement in voicing aspirations with other workers. This analysis uses a descriptive qualitative approach with the analytical method